2014
DOI: 10.1021/cs5015755
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-Catalyzed C–H Activation and Deuteration of Primary Sulfonamides: An Experimental and Computational Study

Abstract: Iridium-catalyzed C−H activation and orthohydrogen isotope exchange is an important technology for allowing access to labeled organic substrates and aromatic drug molecules and for the development of further C−H activation processes in organic synthesis. The use of [(COD)Ir(NHC)Cl] complexes (NHC = N-heterocyclic carbene) in the orthodeuteration of primary sulfonamides under ambient conditions is reported. This methodology has been applied to the deuteration of a series of substrates, including the COX-2 inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(135 citation statements)
references
References 58 publications
7
128
0
Order By: Relevance
“…In previous C-H activation studies, we rationalised observed directing group chemoselectivity using density functional theory (DFT) calculations (see Supplementary Materials for details) to model the relative energies of the binding conformers and subsequent C-H activation pathways [20]. We have now extended this approach to the analysis of the labelling reactions of 12 and 14 (Scheme 7).…”
Section: Theoretical Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…In previous C-H activation studies, we rationalised observed directing group chemoselectivity using density functional theory (DFT) calculations (see Supplementary Materials for details) to model the relative energies of the binding conformers and subsequent C-H activation pathways [20]. We have now extended this approach to the analysis of the labelling reactions of 12 and 14 (Scheme 7).…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Thin layer chromatography was carried out using Camlab silica plates coated with fluorescent indicator UV254 (Sigma-Aldrich), and were visualized using a Mineralight UVGL-25 lamp (Fisher Scientific UK Ltd., Loughborough, UK) or developed using vanillin solution. Catalysts 1a [20], 1b [16], and 1d [18] were prepared according to literature procedures. Esters 6c [32], 10a [33], 10b [34], 10c [35], 10d [36], 10e [37], and 13 [38] were prepared according to the corresponding literature procedures.…”
Section: General Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst we believe that the encumbered nature of the iridium centre within this wider catalyst series is key to the high levels of activity shown, 6 we were conscious that these same steric constraints may disfavour the initial coordination of larger and more tetrahedral directing functional units such as sulfonamides. 7 Having stated this, we were able to induce high levels of incorporation within compound 5i, albeit by moving to a much higher catalyst loading of 50 mol%.…”
Section: Scheme 1 Hydrogen Isotope Exchange Processmentioning
confidence: 85%